(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Traumatic shock is a critical and potentially fatal condition that develops as a result of severe physical injury, most commonly associated with massive hemorrhage, extensive tissue damage, and intense nociceptive stimulation. Despite advances in trauma systems and critical care medicine, traumatic shock remains a major cause of early mortality, particularly in patients with polytrauma. The clinical course of traumatic shock is characterized by rapid hemodynamic deterioration, impaired tissue perfusion, metabolic acidosis, and progressive organ dysfunction. This article provides a comprehensive clinical review of the pathogenesis of traumatic shock, focusing on microcirculatory failure and systemic inflammatory responses. Diagnostic approaches based on clinical assessment, laboratory markers, and imaging modalities are discussed. In addition, contemporary treatment algorithms emphasizing early hemorrhage control, goal-directed resuscitation, and multidisciplinary management are outlined. Early recognition and timely intervention remain the cornerstone of improved survival in traumatic shock.